Fragmentation of Suberin and Composition of Aliphatic Monomers Released by Methanolysis of Cork from Quercus suber L.,Analysed by GC-MS, SEC and MALDI-MS - Bento, M. F.; Pereira, H.; Cunha, M. Á; Moutinho, A. M. C.; van den Berg, K. J.; Boon, J. J.; van den Brink, O.; Heeren, R. M. A. (Holzforschung, 2005)
Suberin from extractive-free cork from Quercus suber L. was depolymerised by methanolysis using different sodium methanolate (NaOMe) concentrations. 1% and 3% NaOMe completely removed suberin from cork (54%–56% of extractive-free cork), but for lower concentrations there was incomplete solubilisation; with 0.05% NaOMe, only approximately 80% of total suberin was removed. The monomeric composition of the extracts differed significantly: for the 0.05% NaOMe, only alkanoic acids and diacids were found; the yield of v-hydroxy acids increased with reactant concentration, as well as alkanols and ferulic acid. Results from light scattering, SEC and MALDI-MS showed that soluble oligomeric fragments containing suberinic acids were present in the methanolysis mixture. The molecular weight of these oligomeric fragments decreased with higher sodium methanolate concentrations.
Keywords: Cork; MALDI-MS; Methanolysis; Quercus suber L.; SEC; Suberin fragmentation

Thermally assisted transmethylation gas chromatography–mass spectrometry of suberin components in cork from Quercus suber L. - Bento, M. F.; Pereira, H. (Phytochemical Analysis, 1998)
Thermally assisted transmethylation gas chromatography - mass spectrometry with tetramethylammonium hydroxide has been applied for the qualitative and quantitative analysis of the suberin fraction of wax-free cork. With this method, hydrolysis of esters together with methylation of carboxylic and hydroxylic groups was observed. Mostly long chain aliphatic components, such as alkanols, alkanoic acids, v-hydroxyacids, v,v-alkanoic diacids, and several 9,10-epoxy and 9,10-dihydroxy forms have been found in keeping with results of other workers in the ﬁeld. Two other components that may give a more complete view of the architecture of suberin were also found, namely the phenolic compound ferulic acid, and glycerol which is probably esteriﬁed to carboxylic groups of the aliphatic building units of suberin
Keywords: Cork; pyrolysis mass spectrometry; Quercus suber; suberin; thermally assisted methylation